FOLDING INSTABILITIES AND CRACKING OF THIN COATINGS ON A SOFT POLYMER SUBSTRATE AS A MODEL OF THE OCEANIC CRUST - Volynskii A.L.; Bazhenov S.L. (My University, 2001)
Nucleation and development of microrelief and fragmentation of coating under tensile extension of polymer films coated with a thin rigid layer is studied, and the mechanisms responsible for the development of both types of structures are discussed. The development of regular folding is controlled by compression-induced buckling instabilities in a rigid coating on a compliant support. Parallel cracks are due to features of mechanical stress transfer from a soft substratum to a rigid coating via an interface. Micro-relief is similar to relief of the oceanic floor in the vicinity of mid-oceanic ridges. We suggest that the young oceanic crust and the upper mantle may behave as a solid coating on a soft basement system.
Keywords: Experimental tectonics; tensional fracture